Comparison of Radial Extracorporeal Shock Wave Therapy and Traditional Physiotherapy in Rotator Cuff Calcific Tendinitis Treatment - Tomris DUYMAZ; Dilşad SİNDEL (Archives of Rheumatology, 2019)
Objectives: This study aims to investigate the efficacy of radial extracorporeal shock wave therapy (rESWT) in relieving pain and improving range of motion (ROM) and functionality besides conventional physiotherapy methods in the treatment of chronic rotator cuff calcific tendinitis (RCCT). Patients and methods: We studied 80 patients (35 males, 45 females; mean age 53.3±9.6 years; range, 40 to 70 years) with chronic RCCT. Patients were randomly divided into two groups: rESWT group (n=40) treated with conventional physiotherapy and rESWT, and control group (n=40) treated only with a conventional physiotherapy program. The traditional physiotherapy program included ultrasound, transcutaneous electrical nerve stimulation, shoulder joint ROM and stretching exercises, and ice applications. All patients received a total of 20 treatments, five days a week for four weeks. rESWT was applied once a week for four weeks in total. Before and after treatment, all patients were evaluated for age, height, weight, Body Mass Index (BMI), pain intensity with a Visual Analog Scale, shoulder ROM, and functional disability status with the shortened version of the Disabilities of the Arm, Shoulder and Hand questionnaire (QuickDASH). Results: Mean BMI value of the participants was 26.1±3.0 kg/m2. Although all parameters of the patients in both groups improved significantly, patients in the rESWT group had a statistically significant improvement in pain, ROM and QuickDash scores (p<0.001, p<0.001, and p<0.001, respectively). Conclusion: We assume that rESWT is an effective and noninvasive method of reducing pain and increasing ROM and functional status without the need for surgery.